Records of digger wasps from Eastern Siberia and the Far East of Russia (Hymenoptera: Sphecidae, Crabronidae) - Jacobs, Hans-Joachim; Liebig, Wolf-Harald (Contributions to Entomology = Beiträge zur Entomologie, 2018)
Information is given on the distribution of 17 species of Sphecidae and 106 species of Crabronidae in Eastern Siberia and the Russian Far East. First records for Eastern Siberia are Crossocerus (Crossocerus) tarsatus (Shuckard, 1837), Diodontus handlirschi Kohl, 1888, Gorytes albidulus (Lepeletier, 1832), Gorytes procrustes Handlirsch, 1888, Nysson interruptus (Fabricius, 1798), Oxybelus haemorrhoidalis Olivier, 1812 and Pemphredon lethifer (Shuckard, 1837). First recorded from Far East is Ectemnius (Ectemnius) guttatus (Vander Linden, 1829).